Dynamic multi-omics mechanisms underpinning retinol tolerance: stage-specific reconstruction of skin barrier function and host–microbiome metabolic interactions - Huang, Yixuan; Zhou, Qi; Gui, Minyan; Guo, Danni; Cheng, Jingmin; Ma, Wentao; Shu, Peng; Liu, Xiao (Frontiers in Microbiology, 2025)
BackgroundRetinol remains an essential component in anti-aging skincare; however, a subset of users develop intolerance, characterized by compromised barrier integrity and inflammation. The temporal dynamics of how skin microbiota and host metabolism co-evolve during retinol tolerance establishment remain poorly understood.MethodsWe conducted a prospective 28-day longitudinal study with 18 Chinese women (aged 25–40): 9 retinol-intolerant subjects monitored at baseline, adverse reaction phase, and tolerance establishment, while baseline data from 9 retinol-tolerant individuals served as controls. We integrated cutaneous phenotypic measurements, metagenomic sequencing, and untargeted metabolomics.ResultsIn the intolerant group, skin phenotype assessment revealed a distinct biphasic response—an acute phase marked by increased stratum corneum hydration, reduced sebum secretion, lower skin pH, and improved wrinkle metrics, followed by a re-equilibration phase characterized by sustained barrier restoration. Metagenomic profiling of 969 microbial species demonstrated that, although overall microbial α-diversity remained stable across time points in both groups, key taxa in the intolerant group exhibited transient “rise-and-fall” dynamics. At baseline, the intolerant group exhibited overrepresentation of Cutibacterium acnes, whereas the tolerant group was enriched in potentially protective species, including Sphingomonas hankookensis and Acinetobacter johnsonii. Untargeted metabolomics showed marked temporal fluctuations with an initial phase of metabolic turbulence, followed by partial recovery. During the early adverse reaction phase in intolerant subjects, lipid and fatty acid metabolic pathways—specifically, glycerophospholipid, linoleic acid, α-linolenic acid, and ether lipid metabolism—were significantly upregulated, concomitant with the suppression of TCA cycle and sphingolipid activity. Conversely, as tolerance was established, enhanced activity in the TCA cycle, sphingolipid, ascorbate, and pentose metabolism pathways—coupled with a reduction in pro-inflammatory arachidonic acid derivatives-indicated metabolic reconstitution and restoration of barrier integrity.DiscussionIntegrated multi-omics correlation analyses further underscored the tightly interconnected regulation of host-microbe energy metabolism, antioxidant defenses, and membrane repair in response to retinol-induced stress. These findings elucidate the temporal interplay between host and microbial processes underpinning retinol tolerance and highlight baseline biomarkers that may facilitate personalized skincare interventions.